Lean Accounting in Transforming the Organizational Culture in PT. A - Sugianto W, Andreas; Pontjoharyo, Wiyono (IJRDO - Journal of Business Management, 2020)
The current business environment is considered to be unstable, uncertain, complex, and ambiguous. Transformation is no longer a choice but a necessity. Lean, which is an operations management concept, has been widely adopted including to accounting. In fact, if the business does not prepare for proper implementation, all the benefits cannot be obtained. Organizational culture has been found to be very important in shaping the success of business. However, a traditional organizational culture is also not capable of sustaining the long-term success of lean accounting. Increased income, cost avoidance, and time and cost efficiency were obtained from lean accounting success implementation. The most important thing is that a supportive organizational culture can make lean implementation deeper, into a mindset and reflected in the actions of all people in the organization so that business entities remain adaptive in industrial changes.